Skills in communication and journalism: a common Latin American base - Roveda Hoyos , Antonio (2024)
This research revealed the common competencies of the disciplinary component of professional academic programs in Communication and/or Journalism in Latin America: Argentina, Mexico, and Colombia cases. Its relevance lies in contributing to the design of tools, methods and indicators that improve the quality of higher education in Latin America, based on the study of training and evaluation processes by competencies. In addition, it provides guidelines for the homologation and validation of studies at a national and international level. The methodology included five steps: 1) Selection of higher education institutions. 2) Selection of academic programs. 3) Identification of competencies declared by the programs. 4) Categorization of competencies in the syllabi of disciplinary subjects. 5) Characterization of common competencies in disciplinary component subjects. It was concluded:1) Break with the prevalence of traditional cognitive competence. 2) Dialogue between dimensions of the integral professional. It was concluded: 1) A solid basis for evaluating the quality of education. 2) Need to promote dialogue between peers, self-knowledge and self-regulation.